Research on the Artistic Aesthetics of Murals in the Tombs of Xianbei Nobility (A Case Study of the XuXianxiu and Lou Rui Tombs) - Borjigin, Khuchit; Dorjsuren, Uranchimeg; Oidov, Khishigbat (Mongolian Journal of Arts and Culture, 2025)
At the dawn of the new century, a significant discovery was made related to the history of nomadic representational art. Unearthed in the year 2000, this tomb has been preserved more completely than the Lou Rui tomb murals discovered and studied in the 1980s. This find is located in the vicinity of present-day Taiyuan City, Shanxi Province, in the People’s Republic of China. The tomb murals of Xu Xianxiu and Lou Rui are notable not only for their innovative techniques in nomadic painting but also for their comprehensive reflection of the social conditions of the era, the interactions among ethnic groups, and the profound content of cultural exchange. Through this research, which focuses on three main areas—compositional features, representational content, and methodological innovation—and is based on archaeological findings and written sources, the artistic characteristics and historical value of the Xianbei tomb murals have been clearly elucidated. Сяньбичуудын бунхны ханын зургийн уран сайхны судалгаа (Шюй Шяньшю болон Лөү Рүй бунхны жишээн дээр) Хураангуй: Шинэ зууны босгон дээр нүүдэлчдийн дүрслэх урлагийн түүхэнд холбогдох нэгэн маш чухал олдвор илэрсэн билээ. 2000 онд илэрсэн энэхүү бунхан нь өмнөх зууны 80-аад онд илрүүлэн судалсан Лөү Рүй бунхны ханын зургаас илүү бүрэн бүтэн хадгалагдан үлдсэн байна. Энэхүү олдвор нь одоогийн БНХАУ-ын Шаньси мужийн Тайюань хотын орчимд байгаа юм. Шюй Шяньшю болон Лөү Рүйн бунхны ханын зургууд нь нүүдэлчдийн уран зургийн арга техникийн шинэчлэлээр зогсохгүй, тухайн үеийн нийгмийн төрх байдал, үндэстнүүдийн харилцан нөлөөлөл, соёлын солилцооны гүн гүнзгий агуулгыг нэгэн цогцоор тусган харуулсан байдгаараа онцлог. Энэхүү судалгаагаар зохиомжийн онцлог, дүрслэлийн агуулга, арга барилын шинэчлэл гэсэн гурван үндсэн судалгааны чиглэлээр археологийн олдвор болоод бичгийн эх сурвалж дээр тулгуурлан дүн шинжилгээ хийснээр Сяньбичуудын бунхны ханын зургийн урлагийн онцлог, түүхэн үнэ цэнийг тодруулсан болно. Түлхүүр үгс: Сяньби, бунхны ханын зураг, урлагийн онцлог, түүхэн үнэлэмж